2009
DOI: 10.1007/s00204-009-0450-y
|View full text |Cite
|
Sign up to set email alerts
|

Subacute exposure to N-ethyl perfluorooctanesulfonamidoethanol results in the formation of perfluorooctanesulfonate and alters superoxide dismutase activity in female rats

Abstract: Perfluorooctanesulfonamides, such as N-ethyl perfluorooctanesulfonamidoethanol (N-EtFOSE), are large scale industrial chemicals but their disposition and toxicity are poorly understood despite significant human exposure. The hypothesis that subacute exposure to N-EtFOSE, a weak peroxisome proliferator, causes a redox imbalance in vivo was tested using the known peroxisome proliferator, ciprofibrate, as a positive control. Female Sprague-Dawley rats were treated orally with N-EtFOSE, ciprofibrate or corn oil (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 81 publications
(156 reference statements)
3
41
0
Order By: Relevance
“…Some PFOS-precursors like N-Et-FOSA and N-Et-FOSE, have shown low conversion factors b1% in rats and trout (Xu et al, 2004;Tomy et al, 2004) or have not yet been studied. However, in 2003, Seacat et al reported a conversion factor to PFOS of up to 20% in a study where rats were exposed long term to N-Et-FOSE; an observation confirmed subsequently by Xie et al (2009). Although the reported levels of PFOS-precursors are generally lower and their physicochemical properties differ from those of PFOS, a variety of them have been detected in water (Ahrens et al, 2009), in indoor and outdoor air (Shoeib et al, 2005;Jahnke et al, 2007), in packaged food (Tittlemier et al, 2006), and in live organisms (from mussels to bald eagles) and waterbird eggs Wang et al, 2008).…”
Section: Indirect Sources Of Human Exposure To Pfosmentioning
confidence: 84%
“…Some PFOS-precursors like N-Et-FOSA and N-Et-FOSE, have shown low conversion factors b1% in rats and trout (Xu et al, 2004;Tomy et al, 2004) or have not yet been studied. However, in 2003, Seacat et al reported a conversion factor to PFOS of up to 20% in a study where rats were exposed long term to N-Et-FOSE; an observation confirmed subsequently by Xie et al (2009). Although the reported levels of PFOS-precursors are generally lower and their physicochemical properties differ from those of PFOS, a variety of them have been detected in water (Ahrens et al, 2009), in indoor and outdoor air (Shoeib et al, 2005;Jahnke et al, 2007), in packaged food (Tittlemier et al, 2006), and in live organisms (from mussels to bald eagles) and waterbird eggs Wang et al, 2008).…”
Section: Indirect Sources Of Human Exposure To Pfosmentioning
confidence: 84%
“…A decrease in SOD and CAT hepatic activities was reported by Banudevi et al (2006) in a study with male rats exposed to PCBs. Notwithstanding, in female rats treated with perfluorooctane sulfonate (PFOS), a higher activity was observed in hepatic SOD, whereas CAT activity remained unchanged (Xie et al, 2009). In the present study, alterations in SOD and CAT activities were observed in agreement with the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 94%
“…An accurate assessment of the indirect exposure to PFCAs and PFSAs is currently unfeasible due to largely unknown values for the absorption efficiencies and PK parameters of most PFCA and PFSA precursors. 8,46 Estimations for biotransformation factors of PFAA precursors and absorption efficiencies are usually determined in rodent experiments, [47][48][49] which can hamper extrapolation to human metabolism. 7,48,50 Trudel et al (2008) proposed absorption efficiencies for PFOA and PFOS in humans being 0.66, 0.8 and 0.91, which were estimated from a study in rodents.…”
Section: View Article Onlinementioning
confidence: 99%